Vulnerability leading to mobility: Syrians’ exodus from Turkey - Şirin Öner, N. Aslı; Genç, Deniz (Migration letters, 2015)
Turkey has been a stage for human mobility for many years, yet it did not have a comprehensive migration and asylum regime until recently. Being the worst refugee crisis of the last decades, the Syrian crisis actually had an impact on developing such a regime of which the Law on Foreigners and International Protection (LFIP) is a crucial element. The LFIP provides temporary protection to the Syrians in Turkey. However, it is recently observed that more and more Syrians are leaving the country. Examining their exodus, the present article is seeking answers to the question of “Why are the Syrians desperately trying to leave Turkey?” Two arguments are put forth in the article. First, Turkey’s new migration and asylum regime has not been able to decrease the refugees’ vulnerability because of its “expectation of temporariness”. Secondly, it is argued that Turkey’s “new asylum regime” is in fact “not that new” due to the fact that asylum-seekers coming from non-European countries have been provided a de facto temporary protection. The article reveals that the Syrian refugees are vulnerable in many fields mainly because they are subject to a protection regime marked by temporariness. As the regime is putting them in limbo, they are leaving Turkey. Turkey’s new asylum regime appears not that new after all.